Impact of quaternary prevention as a brief intervention in medical students' clinical decisions: experience from Vietnam - Thi Hoa Vi Tran; Thanh Liem Vo (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
Objective: to evaluate undergraduate medical students' clinical decision-making process after a brief intervention lecture on quaternary prevention (P4). Methods: quantitative self-controlled intervention study carried out with fifth-year medical students of Pham Ngoc Thach University, Hochiminh city, Vietnam. The medical students were asked to list their eventual interventions based on three different simulated clinical scenarios. The survey was conducted before and after the intervention. Student's propositions were classified into one of the four groups of prevention, according to Jamoulle's model. Results: 115 students participated, resulting in 211 answered sheets. The interventions proposed by the students were mostly centered on prevention groups 1, 2 and 3; the three clinical scenarios partially explained student's intentions of counseling, screening and palliative care. Comparing the data of second phase survey, the intervention was associated with changes in students' aptitude on clinical decision-making, which was especially more important for prevention group 1 (OR = 7.5) and prevention group 4 (OR = 30.05). There was no statistically significant difference in changing students' decision for prevention group 2 (OR = 0.95 p = 0.466) and prevention group 3 (OR = 2.29 p = 0.932). Conclusion: introducing quaternary prevention to the undergraduate medical course can help to steer clinical decisions toward primary prevention and to avoid inappropriate medical interventions.